(untitled) (Albayan Scientific Journal, 2023)
: A Mobile Ad-Hoc Network (MANET) is a self-configuring network of mobile nodes connected by wireless links to form an arbitrary topology without the use of existing infrastructure. In this paper, I have studied the effects of various mobility models on the performance of one routing Destination Sequenced Distance Vector (DSDV Proactive Protocol). I have considered two mobility scenarios for experiment purposes: (Random Wayward and Freeway ) Mobility models. This study aims to determine which appropriate speed is suitable with DSDV protocol when I applied it on (Random Wayward and Freeway) Mobility models, with different speeds. Experiment results illustrate that the performance of the routing protocol varies across different mobility models and different speeds on the mobile node.